Sexuality and Severe Autism : a Practical Guide for Parents, Caregivers and Health Educators. - Reynolds, Kate E. (Jessica Kingsley Publishers, 2013)
Sexual health and sexuality can be difficult subjects for parents and caregivers to broach with autistic children, made more challenging when children are at the severe end of the autism spectrum. Some parents may even question the validity of teaching sexuality to those who are severely autistic. This practical handbook guides you through the process of teaching about sex and sexuality, answering all of the most crucial questions, including: Why is it necessary to teach this subject to my severely autistic child? When is the right time to start talking about these issues? How detailed and expl.